Multicomponent Peptide Hydrogels as an Innovative Platform for Cell-Based Tissue Engineering in the Dental Pulp - Marina E. Afami; Ikhlas El Karim; Imad About; Anna D. Krasnodembskaya; Garry Laverty; Fionnuala T. Lundy (MDPI AG, 2021)
In light of the increasing levels of antibiotic resistance, nanomaterials and novel biologics are urgently required to manage bacterial infections. To date, commercially available self-assembling peptide hydrogels have not been studied extensively for their ability to inhibit micro-organisms relevant to tissue engineering sites such as dental root canals. In this work, we assess the biocompatibility of dental pulp stem/stromal cells with commercially available multicomponent peptide hydrogels. We also determine the effects of dental pulp stem/stromal cell (DPSC) culture in hydrogels on growth factor/cytokine expression. Furthermore, to investigate novel aspects of self-assembling peptide hydrogels, we determine their antimicrobial activity against the oral pathogens Staphylococcus aureus, Enterococcus faecalis, and Fusobacterium nucleatum. We show that self-assembling peptide hydrogels and hydrogels functionalized with the adhesion motif Arg-Gly-Asp (RGD) are biocompatible with DPSCs, and that cells grown in 3D hydrogel cultures produce a discrete secretome compared with 2D-cultured cells. Furthermore, we show that soluble peptides and assembled hydrogels have antimicrobial effects against oral pathogens. Given their antibacterial activity against oral pathogens, biocompatibility with dental pulp stem/stromal cells and enhancement of an angiogenic secretome, multicomponent peptide hydrogels hold promise for translational use.